The effect of silver nanoparticles covered with the Achillea biebersteinii plant extract on angiogenesis of chick chorioallantoic membrane - Parisa Zamani-Esmati; Javad Baharara; Alireza Iranbakhsh; Tayebe Ramezani (Fiyz̤, 2018)
Background: Angiogenesis is a major event in many diseases such as cancer. Today, using silver nanoparticles in industry and medicine has taken into consideration. The Achillea biebersteinii extract has antibacterial, anti-inflammatory and antioxidant effects. The present study aimed at examining the effects of silver nanoparticles coated with the A. biebersteinii extract on angiogenesis of chick chorioallantoic membrane. Materials and Methods: In this experimental study, 50 fertilized eggs Ross were randomly divided into 5 groups: the sham and experimental groups 1 to 4. In the second day of incubation, the window was opened on eggs and the eggs were treated with 50, 100, 150 and 200 μg/mL silver nanoparticles. At the twelfth day, the samples were photographed and the number and lengths of vessels around the sponges, the length of crown-rump, fetal weight and blood vessels' hemoglobin levels were recorded and compared with the control group. Results: The results showed that the 50 μg/mL of silver nanoparticles had no significant effect on the angiogenesis process. However, 100,150 and 200 μg/mL of the nanoparticles doses-dependently decreased the number, length and content of hemoglobin in the blood vessels. Also, fetal weight and crown-rump in concentrations 150 and 200 μg/mL showed a significant decrease compared with the control group (P<0.01). Conclusion: Silver nanoparticles coated with A. biebersteinii extracts can be considered in the studies of diseases associated with angiogenesis such as cancer.